2014
DOI: 10.1007/s00348-014-1829-y
|View full text |Cite
|
Sign up to set email alerts
|

The impact of twine/mesh ratio on the flow dynamics through a porous cylinder

Abstract: The impact of the twine/mesh ratio on the flow through a porous hollow cylinder of diameter D has been experimentally investigated at Reynolds number Re = 800 with a surface porosity varying from 0.67 to 0.90. Our porous cylinder models are inspired by aquaculture pens in that they have similar geometries, and porosities, to those nets commonly used within the aquaculture industry. We show that the surface porosity alone is not the key parameter determining the flow topology of the model, but rather a non-dime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 36 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…The results, in contrast to Takeuchi et al (2007), indicated that the wake characteristics changed toward the wake characteristics of a solid cylinder at a porosity just below 75%. Levy et al (2014) argued that the surface porosity was not the key parameter in defining the flow topology of a porous screen, rather, a non-dimensional parameter based on the twine thickness, mesh hole size and cylinder diameter might influence their experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The results, in contrast to Takeuchi et al (2007), indicated that the wake characteristics changed toward the wake characteristics of a solid cylinder at a porosity just below 75%. Levy et al (2014) argued that the surface porosity was not the key parameter in defining the flow topology of a porous screen, rather, a non-dimensional parameter based on the twine thickness, mesh hole size and cylinder diameter might influence their experimental data.…”
Section: Introductionmentioning
confidence: 99%
“…The results indicated that the wake characteristics changed toward the wake characteristics of a solid cylinder at a porosity just below 75%. [9].…”
Section: Introductionmentioning
confidence: 99%